Molecular evaluation of the presence of Perkinsus spp in samples of scallops (Argopecten purpuratus) from northern Peru - Vivanco S., Manuela (2020)
The aim of this study was to evaluate the presence of Perkinsus spp, a parasite that is mandatory to be report to the OIE, in samples of calico scallop (Argopecten purpuratus) from Ancash, Peru, using the PCR technique. In total, 56 samples were selected from those collected for a previous study in 2015. The selected samples were gill tissues with histological lesions suggestive of infection with the protozoan (hemocytic infiltration and necrosis). DNA was extracted from the samples and specific primers were used to detect Perkinsus spp by PCR. In addition, the detection limit of the technique was evaluated. All samples were negative. It was determined that 1.63 ng was the least detectable template DNA in one of the positive controls.